The Application of the Snowball Throwing Learning Model Based on HOTS Questions in Improving Islamic Religious Education Learning Outcomes at Junior High School - Mazidah, Rizkyna; Romadlon, Dzulfikar Akbar; Astutik, Anita Puji (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to determine the increase in learning outcomes and to train students to think creatively and actively use the snowball-throwing learning model in PAI class VII at SMPN 1 Tanggulangin. This research uses a type of classroom action research (CAR), carried out in three cycles with four stages, namely planning, implementation, observation, and reflection, carried out repeatedly. The subjects in this study were 36 students in classes VII-6. Data collection techniques using observation, interviews, tests, and documentation. Data analysis technique using descriptive analysis. This research shows that implementing the HOTS question-based Snowball Throwing learning model in the chapter "Al-Qur'an and Sunnah as a guide to life" obtained an average student learning completeness with a percentage of 80.00% which can be declared successful with a moderate learning achievement score students of 80.06. In addition, the use of HOTS questions can affect the level of students' critical thinking and learning outcomes. Likewise, the increase in class activity in the first cycle was 78.57%. In the second cycle, it increased by 85.71%; in the third cycle, it reached 92.86%. This study considered it successful if 80% of students achieved the minimum criteria for completeness. The application of the HOTS question-based Snowball throwing learning model in PAI subjects at SMPN 1 Tanggulangin was successful, as seen from the increase in the average value of students in each cycle.